Fidaxomicin: A new fight against clostridium difficile-associated diarrhea - Dick B. S. Brashier; Amol Khanapure; A K Sharma (Wolters Kluwer Medknow Publications, 2014)
Clostridium difficile-associated diarrhea (CDAD) occurs commonly as a side effect of broad-spectrum antibiotics. Drugs approved for CDAD are only two of them, metronidazole and vancomycin. Most promising drug for treatment of CDAD is vancomycin, but due to emergence of hypervirulent strains, outcomes have become poor. Fidaxomicin has being approved lately for treatment of CDAD, which has shown good results as compared to vancomycin. Fidaxomicin inhibits protein synthesis by inhibiting transcription carried out by sigma subunit of RNA polymerase. Fidaxomicin has been seen to be a well tolerated, with minimal adverse effects. Clinical trials has showed that fidaxomicin has similar results to vancomycin in showing clinical response, whereas it was superior to vancomycin in having sustained clinical effect, in CDAD.